2021
DOI: 10.1111/jmwh.13209
|View full text |Cite
|
Sign up to set email alerts
|

A Group Videoconference Intervention for Reducing Perinatal Depressive Symptoms: A Telehealth Pilot Study

Abstract: Introduction Perinatal depression occurs in 12% to 18% of childbearing women. Telehealth is a promising platform for delivering perinatal mental health care, particularly during a pandemic when in‐person services have been significantly curtailed. However, there is little research to document the feasibility of telehealth to address perinatal depression. This pilot study evaluated the feasibility and preliminary results of an 8‐week facilitated group videoconference intervention. Methods The study enrolled pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
(87 reference statements)
0
19
0
2
Order By: Relevance
“…authors argued that the transition to telehealth was disruptive to consistency of care, which this high-risk group of pregnant women with opioid use difficulties particularly required (McKiever et al, 2020). A small study piloting the delivery via videoconferencing of an effective in-person mindfulness-based cognitive behavioral therapy (CBT) group for women in the perinatal period for treatment of postpartum depression found that delivery via virtual format was effective based on results of decrease in Edinburgh Postnatal Depression Scale (EPDS) pre-and post-intervention (Latendresse et al, 2021). Notably, public awareness of health disparities and societal inequities has increased due to the disproportionate impact of the COVID-19 pandemic on people of color, especially, Black, Hispanic, Native American, and Asian populations being up to 3.4 times more likely to be hospitalized due to COVID-19 than their White counterparts (CDC, 2021;Rubin-Miller et al, 2020).…”
Section: Key Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…authors argued that the transition to telehealth was disruptive to consistency of care, which this high-risk group of pregnant women with opioid use difficulties particularly required (McKiever et al, 2020). A small study piloting the delivery via videoconferencing of an effective in-person mindfulness-based cognitive behavioral therapy (CBT) group for women in the perinatal period for treatment of postpartum depression found that delivery via virtual format was effective based on results of decrease in Edinburgh Postnatal Depression Scale (EPDS) pre-and post-intervention (Latendresse et al, 2021). Notably, public awareness of health disparities and societal inequities has increased due to the disproportionate impact of the COVID-19 pandemic on people of color, especially, Black, Hispanic, Native American, and Asian populations being up to 3.4 times more likely to be hospitalized due to COVID-19 than their White counterparts (CDC, 2021;Rubin-Miller et al, 2020).…”
Section: Key Findingsmentioning
confidence: 99%
“…This may produce competing needs during the time of telehealth visits with attending to other children. Latendresse et al (2021) found in their study that one cause of intervention dropout, or nonparticipation after starting a group, was reported by participants to be due to ". .…”
Section: Implications For Practicementioning
confidence: 99%
See 2 more Smart Citations
“…In 2012 the Institute of Medicine (23) addressed the need to evaluate the effectiveness of telehealth and urged researchers and funding bodies to follow the recommendations (24) to include "the use of more naturalistic methods and settings," and "better standardization of populations, interventions, and outcome measures." To address this issue, we evaluated a group videoconference intervention (VCI) to deliver mental health services to women with mild to moderate PD symptoms (25). The purpose of our subsequent qualitative study was to obtain the perspectives of the women who participated in these groups.…”
Section: Introductionmentioning
confidence: 99%